2021
DOI: 10.1002/bbb.2177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the co‐digestion of agricultural lignocellulosic residues with manure from South American camelids

Abstract: This study aims to evaluate the effects of the co‐digestion of agricultural residues with manure from camelids from the Andean zone. Different combinations of llama manure (LM) and vicuñas (VM) were made with amaranth (AS), quinoa (QS), and wheat (WS) residues. They were fermented using sewage sludge as inoculum. The co‐digestion was evaluated under mesophilic conditions for 40 days. The ratios of volatile substances of substrate / co‐substrate evaluated were 0:100; 25:75; 50:50, 75:25, and 100:0. Two substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 83 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…As per one review, the beneficial aspect of an enriched biogas yield of 400% was reported for co-digestion compared to digestion of a sole feedstock [1]. In addition, regardless of the substrate to inoculum ratio, the methane yield increased by 120% with co-digestion of vicuñas (VM) and amaranth (AS) compared to anaerobic digestion of a single substrate, which was higher compared to other studies on co-digestion of animal byproducts with an increment in volatile solid (VS) conversion of about 75% [16]. In this regard, this review paper details the impacts of a co-substrate on system performance, various operational parameters, microbe status, and recent achievements.…”
Section: Introductionmentioning
confidence: 76%
“…As per one review, the beneficial aspect of an enriched biogas yield of 400% was reported for co-digestion compared to digestion of a sole feedstock [1]. In addition, regardless of the substrate to inoculum ratio, the methane yield increased by 120% with co-digestion of vicuñas (VM) and amaranth (AS) compared to anaerobic digestion of a single substrate, which was higher compared to other studies on co-digestion of animal byproducts with an increment in volatile solid (VS) conversion of about 75% [16]. In this regard, this review paper details the impacts of a co-substrate on system performance, various operational parameters, microbe status, and recent achievements.…”
Section: Introductionmentioning
confidence: 76%
“…Several studies have explored the application of anaerobic digestion to guinea pig manure [15,20]. These investigations highlight that anaerobic digestion (AD) holds significant potential for reducing farm waste while simultaneously offering an alternative means to fulfill local energy requirements by converting guinea pig manure into biogas [21].…”
Section: Introductionmentioning
confidence: 99%